THE USE OF CODE SWITCHING AND CODE MIXING BY INDOFOOD AND UNILEVER FOOD ADVERTISEMENTS ON TELEVISION - Najihatul Fitri; Adhis Darussalam Pamungkas (Universitas Indraprasta PGRI, 2022)
The aims of the research are to find out the type, function and reason of code switching and code mixing mostly used by Indofood and Unilever Food Advertisements on Television. The research design of this research is descriptive qualitative because the result of the data analyzed is in descriptive phenomenon such as words, sentence and utterance while the research method used in this research is library research. The result findings are: 1). The type of code switching mostly used here is intra sentential switching which occurs 36 times. While the type of code mixing mostly used here is intra sentential mixing which occurs 38 times. 2). The function of code switching and code mixing mostly used here is metalinguistic function which occurs 60 times. 3). The reason of code switching and code mixing mostly used here is talking about particular topic which occurs 48 times.